Pengaruh pemberian sari kurma dan sari kacang hijau terhadap peningkatan ASI pada ibu nifas di klinik Kurnia Ningsih Kabupaten Deli serdang tahun 2022 - Gf Gustina Siregar (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
ABSTRACK The postpartum period is the period after the baby is born, when the placenta and amniotic sac must return the organs in the uterus to their pre-pregnancy period, which lasts about six weeks. Breast milk is a liquid that has a very complex content and is needed for a baby to optimize its growth and development. Dates consumed during pregnancy are believed to strengthen the fetus in the womb and also facilitate the delivery process The content of mung bean juice consumed by the mother becomes additional food that can meet the nutritional needs of nursing mothers so that the quality and volume of breast milk increases so that it supports the growth and development of the baby. This study aims to determine the effect of giving date palm juice and green bean juice to increase breast milk production at the Kurunia Ningsi Clinic, Deli Tua District, Deli Serdan Regency in 2022. The research method used was a quasi-experimental approach with a two-group pretest-posttest design. This sampling used a targeted sample and obtained 30 mothers who were interviewed after birth. This research was conducted using the Wilcoxon test. Respondents who were given date extract 93.24% and mung bean extract 86.58% experienced an increase in milk production. The results of the analysis showed that the respondent's milk production was p 0.000 (p < 0.05), indicating that supplementation with date palm juice and mung bean juice increased postpartum mother's milk production. This shows that date palm juice and green bean juice can increase breast milk production in postpartum mothers.